Frequency of musculoskeletal pain and thermal comfort in students of dentistry - Paz, Bruna Katarine Beserra; Rodrigues, Vandilson Pinheiro; Bena, Maryangela Godinho Pereira; Grossi, Débora Bevilaqua; Florêncio, Lidiane Lima; Zago, Patricia Maria Wiziack; Gonçalves, Maria Claudia (Ciência e Natura, 2018)
The objective of this study was to evaluate the frequency of musculoskeletal symptoms (MS) and thermal sensation in the clinical setting in dental students. We evaluated 124 students in the curricular stage. The frequency of MS was evaluated with the Nordic Musculoskeletal Questionnaire and the thermal sensation through reporting by scale ranging from very cold to very hot. About 80% of the students had some MS. The sites with the highest frequency were the regions of the thoracic spine (46%) and neck (45%) (P < 0.001). Neck pain was associated with thermal discomfort (P = 0.02), especially in women. Positive correlations were also observed between the different anatomical regions and intensity of the symptoms (P <0.05), mainly between the thoracic and lumbar spine (Rs = 0.53), knee and ankle/foot (Rs = 0.52), and neck and shoulder (Rs = 0.51) for both sexes. Regarding thermal sensation of the clinical environment, the clinical environment temperature was considered comfortable by 33.9% of the patients. MS are frequent in dentistry students, especially in the spinal region, and pain in the neck region is correlated with thermal sensation of cold, calling attention to the need for the prevention and for ergonomic and lifestyle changes.